2011
DOI: 10.1111/j.1463-1326.2011.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-year glycaemic control and healthcare expenditures following initiation of insulin glargine versus neutral protamine Hagedorn insulin in type 2 diabetes

Abstract: Glargine therapy may be an effective long-term option for improving glycaemic control, with lower rates of hypoglycaemia and healthcare costs in patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Once-daily insulin glargine has been shown to provide at least as effective glycaemic control as NPH insulin, and to be cost effective in a range of countries and settings. [33][34][35][36][37][38][39] Basal insulin analogues have been shown to have several advantages compared with NPH insulin, including less pharmacological variability, a lower risk of hypoglycaemia and a greater impact on quality of life. 18 20 21 40 The rates of hypoglycaemia-related events were, however, similar for insulin glargine and NPH insulin in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Once-daily insulin glargine has been shown to provide at least as effective glycaemic control as NPH insulin, and to be cost effective in a range of countries and settings. [33][34][35][36][37][38][39] Basal insulin analogues have been shown to have several advantages compared with NPH insulin, including less pharmacological variability, a lower risk of hypoglycaemia and a greater impact on quality of life. 18 20 21 40 The rates of hypoglycaemia-related events were, however, similar for insulin glargine and NPH insulin in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many practitioners would use a sulfonylurea as a second drug. Although such agents carry a risk of hypoglycemia, they are available in inexpensive generic forms, there is wide experience with their use, and they may be more cost-effective than other, newer drugs (59,60). Alternatives with less of a risk of hypoglycemia include GLP-1 analogs, DPP-4 inhibitors, thiazolidinediones, SGLT-2 inhibitors, α-glucosidase inhibitors, colesevelam, bromocriptine, and glinides.…”
Section: How Medical Practice Should Changementioning
confidence: 99%
“…Of the reviewed studies nine were considered relevant (Tables 2, 3) [14, 2128]. All studies were industry-sponsored.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were industry-sponsored. Details of the included studies including number of people, treatment setting, study year, study design and follow-up period, mean age, and primary objective, are reported in Table 4 [14, 2128]. …”
Section: Resultsmentioning
confidence: 99%